Outcome of Acute Respiratory Failure Secondary to Engraftment in Children After Hematopoietic Stem Cell Transplant - Elbahlawan, Lama; Morrison, Ray; Li, Ying; Huang, Sujuan; Cheng, Cheng; Avent, Yvonne; Madden, Renee (Frontiers in Oncology, 2020)
Introduction: Respiratory complications due to engraftment syndrome (ES) in the post– hematopoietic stem cell transplant (HSCT) setting can lead to acute respiratory failure (ARF). Outcomes of children developing ARF due to engraftment are unknown. Methods: We conducted a retrospective analysis of 1527 pediatric HSCT recipients and identified children who developed ARF due to ES over a 17-year period. Thirty patients that developed ARF and required invasive mechanical ventilation (IMV) due to ES were included in this study. Results: The survival rate for our cohort was 80% (alive at intensive care unit [ICU] discharge). The most common underlying primary disease was hematologic malignancy, and 67% of children underwent allogeneic HSCT. Further, 73% required vasopressor drips and 23% underwent dialysis. Survivors had a shorter median ICU length of stay than did non-survivors (15 vs 40 days, respectively, p=0.01). Survivors had a significantly lower median cumulative fluid balance on days 4 and 5 after initiation of IMV than did non-survivors (28 vs 140 ml/kg, p=0.038 on day 4, and 18 vs 149 ml/kg, p=0.044 on day 5, respectively). Conclusion: Our results suggest that children who develop ARF during engraftment have better ICU survival rates than do those with other etiologies of ARF post-HSCT. Furthermore, fluid overload contributes to mortality in these children; therefore, strategies to prevent and address fluid overload should be considered.